Sensitizing with short conjugated molecules: multimodal anchoring on ZnO nanoparticles for enhanced electron transfer characteristics, stability and H-2 evolution - George, Leena; Sappati, Subrahmanyam; Ghosh, Prasenjit; Devi, R. Nandini (Catalysis Today, 2018)
Sensitizing semiconductors with organic dyes is usually employed to improve efficiency of semiconductors towards visible light absorption and charge transport. However, till date most of the dyes are either noble metal based with complex and expensive synthesis procedure or have a very narrow absorption band. Further the photostability of the dyes is another important issue. In this work we have studied, using a combination of photophysical and computational methods, ZnO nanoparticles sensitized with transition metal free, cheap and easy to synthesize azoquinoline dye that has been designed to have multiple chelating sites, viz., carboxylic group and hydroxyl imine group as a photocatalyst for water splitting activity. We find that the presence of multiple chelating sites facilitates dual mode of anchoring on ZnO nanoparticles, which leads to enhanced photostability and H-2 generation of the composite. This is attributed to the incorporation of resonance features in the dye that increases electron transfer between ZnO and dye in contrast to the charge accumulation and photo degradation observed in non-conjugated and single site anchoring counterparts. Electron transfer from ZnO to dye under UV light and reverse in visible light could be identified experimentally. Such simple designing aspects can aid in identifying better catalysts for photocatalytic water splitting.